Mitigation of gas pipeline integrity problems - Okyere, Mavis Sika (Boca Raton, FL : CRC Press/Taylor & Francis Group, LLC, 2020)
"This book presents the methodology that will enable an engineer, experienced or not, to alleviate pipeline integrity problems during operation. It explains the principal considerations and establishes a common approach in tackling technical challenges that may arise during gas production. This practical work serves the needs of advanced students, researchers, and professionals working in pipeline engineering and petrochemical industries"--
Chapter 1 IntroductionChapter 2 Third-Party DamageChapter 3 CorrosionChapter 4 Construction and Materials DefectChapter 5 Geotechnical HazardsChapter 6 Off-Spec Natural GasChapter 7 Natural Gas HydrateChapter 8 Leak and Break Detection
OCLC-licensed vendor bibliographic record.
Keywords: Natural gas pipelines -- Reliability; Natural gas pipelines -- Protection; Natural gas pipeline failures -- Prevention; TECHNOLOGY / Petroleum